Penerjemahan Frase Kolokasi Dalam Al-Qur'an - Fitri Nursalam, Yufridal; ana, Sri (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to analyze Arabic collocation patterns in relation to Quranic translation accuracy and to investigate effective strategies and contextual approaches compared with literal approaches in the translation process. The study employs qualitative research methods utilizing linguistic analysis and bibliographic approaches to examine Quranic texts and their various translations, with particular focus on collocation analysis and inter-lexical semantic relationships. The research yields three principal findings. First, collocation translation demonstrates three primary influence patterns: semantic distortion patterns, wherein collocations with non-compositional meanings undergo semantic distortion of up to 65% when rendered literally. Second, the